REFLECTION STUDY OF OVERALL METHOD USING ON ENGLISH GRAND MASTERING AT BACKGROUND FOREHAND AND BACKHAND - Indrayogi Indrayogi (STKIP PGRI Jombang, 2022)
Based on field conditions, the mastery of English grip techniques is still low on forehand and backhand strokes. So it is necessary to do a reflection study using the overall method of each lesson, because a reflection study aims to overcome any weaknesses that arise in students and teachers, making it easier to provide further material. This research is using experimental method. The population of class VII students of SMPN 2 Majalengka, amounting to 407 people with purposive sampling with a sample of 40 people, namely class VII H. The instrument used was a rubric assessment with 4 assessment norms. The data analysis technique used was the chi square test with a significance level of 1%. Based on data analysis, there is an increase of about 57% with the results of the chi square test, it turns out that X2 count = 70.7 X2 table = 18.47, which means that the results of the research using the overall method have an influence on mastery of the English grip on forehand and backhand strokes. Significant research results are also from the application of reflections from each meeting which is able to correct any weaknesses that arise. From the results of calculations and statistical analysis, it is concluded that: That the reflection study has an influence on the use of the overall method on the mastery of the English grip technique on forehand and backhand strokes in badminton.